Multiple Myeloma with Ovarian Plasmacytoma Mimicking Ovarian Carcinoma with Metastasis: A Case Report - Agarwal, Shivangi; Gothwal, Ravinder Singh; Sharma, Vishnu; Jain, Sandeep (Asian Pacific Journal of Cancer Care, 2021)
Ovarian involvement in multiple myeloma is extremely rare. This paper reports a case of a 50-year-old female who presented with lower back and chest pain of one-month duration. Computed tomography imaging showed lytic lesions in the sternum, ribs, thoracic and lumbar vertebrae with a right adnexal mass. On pathological examination, plasmacytoma was confirmed from the adnexal mass. Bone marrow examination revealed plasma cell infiltration in bone marrow with positive light chain IgG lambda type in serum and raised microglobulin. She was finally diagnosed as a case of IgG lambda myeloma with ovarian plasmacytomas (RISS II).